Attenuation of hyperalgesia responses via the modulation of 5-hydroxytryptamine signalings in the rostral ventromedial medulla and spinal cord in a 6-hydroxydopamine-induced rat model of Parkinson's disease. Issue 1 (February 2017) - Wang, Chen-Tao; Mao, Cheng-Jie; Zhang, Xiao-Qi; Zhang, Cai-Yi; Lv, Dong-Jun; Yang, Ya-Ping; Xia, Kai-Lin; Liu, Jun-Yi; Wang, Fen; Hu, Li-Fang; Xu, Guang-Yin; Liu, Chun-Feng
Background: Although pain is one of the most distressing non-motor symptoms among patients with Parkinson's disease, the underlying mechanisms of pain in Parkinson's disease remain elusive. The aim of the present study was to investigate the role of serotonin (5-hydroxytryptamine) in the rostral ventromedial medulla (RVM) and spinal cord in pain sensory abnormalities in a 6-hydroxydopamine-treated rat model of Parkinson's disease. Methods: The rotarod test was used to evaluate motor function. The radiant heat test and von Frey test were conducted to evaluate thermal and mechanical pain thresholds, respectively. Immunofluorescence was used to examine 5-hydroxytryptamine neurons and fibers in the rostral ventromedial medulla and spinal cord. High-performance liquid chromatography was used to determine 5-hydroxytryptamine and 5-hydroxyindoleacetic acid levels. Results: The duration of running time on the rotarod test was significantly reduced in 6-hydroxydopamine-treated rats. Nociceptive thresholds of both mechanical and heat pain were reduced compared to sham-treated rats. In addition to the degeneration of cell bodies and fibers in the substantia nigra pars compacta, the number of rostral ventromedial medulla 5-hydroxytryptamine neurons and 5-hydroxytryptamine fibers in the spinal dorsal horn was dramatically decreased. 5-Hydroxytryptamine concentrations in both the rostral ventromedial medulla and spinal cord were reduced. Furthermore, the administration of citalopram significantly attenuated pain hypersensitivity. Interestingly, Intra-rostral ventromedial medulla (intra-RVM) microinjection of 5, 7-dihydroxytryptamine partially reversed pain hypersensitivity of 6-hydroxydopamine-treated rats. Conclusions: These results suggest that the decreased 5-hydroxytryptamine contents in the rostral ventromedial medulla and spinal dorsal horn may be involved in hyperalgesia in the 6-hydroxydopamine-induced rat model of Parkinson's disease.